Are genes of interleukins’ 10 (RS1800872) and heat shock protein 70-2 (RS1061581) predictive markers of cytokines production in patients with enterocolitis - Syrota, B. V.; Sydorchuk, L. P. (Journal of Education, Health and Sport, 2018)
Objective: to investigate the effect of 1267 AG gene polymorphism of heat shock proteins (HSP) family 70-2 (HSP70-2) and C-592A gene polymorphism of interleukin 10 (IL-10) on the level IL-1β, TNF- and IL-10 in the blood of patients with colienteritis. Materials and methods: 95 patients suffering from Colienteritis participated in the study including 34.74% (33) men, and 65.26% (62) women, their average age was 38.66±3.11 years. Concentration of IL-1β, TNF- та IL-10 in the blood plasma was examined by means of immune-enzyme method. Polymorphism of HSP70-2 (rs1061581) and IL-10 (rs1800872) genes was studied by means of polymerase chain reaction (PCR) method. The control group included 30 practically healthy individuals correlated by their age and sex who were not infected by diseases of any localization during the last 6 months. Results. Changes of immune-inflammatory body response in patients with colienteritis are characterized by an increased synthesis of the first generation pro-inflammatory IL-1β and TNFα on 40.93% and 44.44% (р<0.001) respectively against the ground of low production of anti-inflammatory IL-10 – on 37.30% (р<0.001) and are indicative of certain mechanisms of specific immune response formation: imbalance between a high activity of the immune cellular link at the expense of Тh1 lymphocytes and macrophages/monocytes, and insufficient activity of the humoral link due toТh2 system and B-lymphocytes activity. Single-factor dispersive analysis confirmed the association between the gene promoter of heat shock protein HSP70-2 (1267AG) and increased level of IL-1β in the blood, more considerable in the carriers of GG-genotype on 45,05% (F=11.66; p<0.001), and decreased concentration of IL-10 (F=4.56; p=0.035), more considerable in the carriers of GG-genotype on 23.38% (р=0.031). On the contrary, promoter of IL-10 (C-592A) gene is associated only with decreased content of IL-10 (F=3.14, p=0.048), the most substantial in the carriers of mutation A-allele on 26.95% and 20.64% (р<0.05) respectively. Conclusions: Availability of GG-genotype of HSP70-2 gene in patients with Colienteritis is associated with a higher content of IL-1β increase in the blood plasma and a low concentration of IL-10. Occurrence of A-allele of IL-10 gene in the genotype of patients with Colienteritis is characterized by the lowest IL-10 content.